Occupy and Education: Introduction - Entin, Joseph; Ohmann, Richard; O’Malley, Susan (Radical Teacher, 2013)
We were inspired by Occupy Wall Street (OWS) and the rapid spread of Occupy across the United States and beyond. The commune-like camp sites, the general assemblies and use of the people’s mic, the marches and demonstrations, the provocative refusal to issue demands, the proliferation of working groups and spokes councils, the creative explosion of revolutionary slogans and art, the direct condemnation of corporate finance and of the massive inequalities that structure our society, the “free university” teach-ins, the campaigns against foreclosure and debt—all these elements of Occupy gave us new hope that radical change might happen in our time.